Market‐led options to scale up legume seeds in developing countries: Experiences from the Tropical Legumes Project. (9th July 2019) - Rubyogo, Jean‐Claude; Akpo, Essegbemon; Omoigui, Lucky; Pooran, Gaur; Chaturvedi, Sushil Kumar; Fikre, Asnake; Haile, Desmae; Hakeem, Ajeigbe; Monyo, Emmanuel; Nkalubo, Stanley; Fenta, Berhanu; Binagwa, Papias; et al.
Abstract: There are several hurdles to ensure sustainable seed production and consistent flow of improved legume varieties in sub‐Saharan Africa (SSA) and South Asia (SA). The unreliable demand, autogamous nature of most of the grain legumes, and slow variety replacement rate by smallholder farmers do not provide strong incentive for private seed companies to invest in legume seed business. Unless a well thought‐out and comprehensive approach to legume seed delivery is developed, current seed shortages will continue, eroding emerging market opportunities. The experiences reported here are collated through a 10‐year partnership project, the Tropical Legumes in SSA and SA. It fostered innovative public–private partnerships in joint testing of innovative market‐led seed systems, skills and knowledge enhancement, de‐risking private sector initiatives that introduced in new approaches and previously overlooked entities in technology delivery. As new public and private seed companies, individual seed entrepreneurs and farmer organizations emerged, the existing ones enhanced their capacities. This resulted in significant rise in production, availability and accessibility of various seed grades of newly improved and farmer demanded legume varieties in the target countries.